2014
DOI: 10.4163/jnh.2014.47.5.351
|View full text |Cite
|
Sign up to set email alerts
|

Developing and testing the reliability of a measurement tool for an urban area food environment in Korea: Focusing on food stores

Abstract: Purpose: The aim of this study was to develop a reliable measurement tool to assess the urban food environment, particularly focusing on food stores in Korea. Methods: The items for the measurement tool were selected through systematic literature reviews and adjusted to the Korean food environment. A total of 25 food stores in an urban area were recruited for the pilot test to evaluate the time required for completion of the survey, ease of response, willingness to participate, difficulties in conducting the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Previous studies have developed and evaluated measurement tools for the food environment, which commonly address factors such as the availability, accessibility, acceptability, price, and quality of food, with a focus on grocery stores within the local community [11][12][13][14]17]. In particular, Caspi et al proposed five key domains of the local community food environment, which were identified through systematic review, including availability, accessibility, affordability, accommodation, and acceptability [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have developed and evaluated measurement tools for the food environment, which commonly address factors such as the availability, accessibility, acceptability, price, and quality of food, with a focus on grocery stores within the local community [11][12][13][14]17]. In particular, Caspi et al proposed five key domains of the local community food environment, which were identified through systematic review, including availability, accessibility, affordability, accommodation, and acceptability [6].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, low-income individuals use cheaper grocery stores rather than the nearest grocery store [16]. A food environment measurement tool has been developed for older adults living in urban South Korea, which measured factors including how grocery stores operate, accessibility via public transportation, the availability of delivery and phone ordering, and the number of food items available [17]. However, this comprises many questions and is an objective indicator.…”
Section: Introductionmentioning
confidence: 99%